Asian development outlook (ADO) supplement a firmer growth outlook for Asia. (Asian Development Outlook, 2017)
The unexpectedly strong expansion in Central, East, and Southeast Asia more than offsets a downward adjustment to growth forecasts for South Asia. In 2018, regional growth is expected to slow slightly to 5.8%, as predicted in the Update. Excluding the newly industrialized economies of the Republic of Korea (ROK), Singapore, Taipei,China, and Hong Kong,China, the growth outlook for the region is revised up to 6.5% from 6.4% for 2017 but unchanged at 6.3% for 2018.The collective growth forecasts in the major industrial economies the United States, the euro area, and Japan are revised up to 2.2% from 2.0% for 2017 and to 2.1% from 2.0% for 2018. The upgrade reflects third quarter stronger than expected growth in the euro area, supported by domestic demand, and in Japan by private investment and net exports.